"Aí vindes outra vez, inquietas sombras?...": tempo e memória na tradução de Dom Casmurro para Capitu - Lara Luiza Spagnol Oliveira (2013)
The dissertation focuses on the time question found on the cultural translation of Dom Casmurro by Machado de Assis to the audiovisual adaptation the micro series Capitu, directed by Luiz Fernando Carvalo and exhibited on Rede Globo in 2008. The main purpose is to comprehend how time throughout these works are related to theimage of a time that is constellated, multiple, non linear, heterogeneous and contemporary, as conceited by Walter Benjamin in Teses sobre o conceito de história, and by Giorgio Agamben in O que é o contemporâneo?. The intention is to analyze in which ways these temporal aspects are recreated in the translation of Machado deAssiss romance for the micro series Capitu. Also, there will be a discussion on memory and reminiscence in both works, focusing on the function of these in the making process of the temporal dislocationinside the narratives. In order to do so, it will be used the concept of Nostalghía, proposed by Nádia Seremetakis in The Senses Still.Questions concerning translation theories and images will also be analyzed, using as theorical support the reflections of Didi-Huberman and César Guimarães, regarding the conceptions of image which are also related to a time conception and the propositions of Walter Benjamin and Haroldo de Campos about translations as a creation process